Compassion focused therapy : clinical practice and applications - Gilbert, Paul; Simos, Gregoris (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Compassion Focused Therapy: Clinical Practice and Applications offers evidence-based guidance and extensive insight into the science behind compassion focused therapy. The first section of the book explores the evolution and physiological infrastructures of caring, and how compassion arises when humans use their complex cognitive competencies to address suffering deliberately and intentionally. With this framework and basis, the next sections of the book explore CFT applied to groups, specific interventions such as chair work, the importance of applying the principles of the therapy to oneself, the CFT therapeutic relationship, and a chapter offering a systematic review of the evidence for CFT. The third section offers a series of multi-authored chapters on interventions for a range of different mental health problems such as depression, anxiety, trauma, and many others. Being the first major clinical book on compassion focused therapy, with leading international researchers and clinicians addressing central problems, this landmark publication will appeal to psychotherapists from a variety of schools as well as being a vital resource for compassion focused therapists"--
Keywords: Emotion-focused therapy; Compassion; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health